'Uluum al-Quran 'Inda 'Abdillah bin 'Umar Radhi Allahu 'Anhuma (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2019)
Ulumul Qur'an has been used since the inception of the Qur'an. Along with the process of the Qur'an to perfection, Ulumul Qur'an had also developed along it to these days. At the time, this disipline of knowledge was not well structured neither systematic. Nevertheless, it was used in all conditions, such as science of qiraat, Rasm, asbab al-nuzul and others. In this paper, the authors wanted to collect Ulumul quran from a great companion named Abdullah bin Umar in qiraat, asbab al-nuzul, Nasikh wal Mansukh and Qawaid Tafsir